Catholyte-free electroreduction of CO2 for sustainable production of CO: concept, process development, techno-economic analysis, and CO2 reduction assessment. Issue 6 (9th March 2021) - Lee, Jaeseo; Lee, Wonhee; Ryu, Kyung Hwan; Park, Joungho; Lee, Hyojin; Lee, Jay H.; Park, Ki Tae
Abstract : A sustainable technical alternative for CO production from CO2 and new insights into making the process economically viable are provided based on experimental data. Abstract : Electrochemical CO2 reduction (ECO2 R) is considered as one of the economically viable means to convert CO2 into useful products, for achieving carbon neutrality in the future. Many studies have been conducted on developing and evaluating electrochemical cells that provide high energy efficiency and conversion of CO2 for CO production via ECO2 R. However, commercially feasible technologies are yet to be developed and demonstrated due to various technical limitations as well as the lack of a systematic evaluation framework. In this study, CO production performance is examined by catholyte-free electrochemical CO2 reduction (CF-ECO2 R), which eliminates a large ohmic drop by removing the catholyte compartment, thus lowering the energy requirement. The CF-ECO2 R shows 0.6 V lower cell voltage and 17.4% higher electrical energy conversion efficiency than a typical GDE-catholyte method using 1 M KOH as the catholyte at a current density of 240 mA cm −2 . The obtained results are used to demonstrate its technical feasibility and to provide basic data for the evaluation of a scale-up process. A mathematical model is developed based on the obtained experimental data and the model is simulated along with three different options of downstream separation to provide basic mass and energy balance data. Then, techno-economic and CO2 life cycle analyses are conducted to suggest the best configuration of the overall CO production system in terms of the economics and net CO2 reduction. It is estimated that the best configuration provides a reduction in CO2 emission by 48% compared to the conventional CO production via steam methane reforming. This configuration is also assessed to be economically feasible, giving a production cost (584 USD per ton CO) that is competitive with the current market price of CO. It is also demonstrated that the operating voltage of the CF-ECO2 R and regional influences such as CO2 emission intensity and cost of the mixed electricity strongly affect the cost and CO2 emission of the system.